The Ukrainian night : an intimate history of revolution - Shore, Marci (Yale University Press, 2017)
What is worth dying for? While the world watched the uprising on the Maidan as an episode in geopolitics, those in Ukraine during the extraordinary winter of 2013-14 lived the revolution as an existential transformation: The blurring of night and day, the loss of a sense of time, the sudden disappearance of fear, the imperative to make choices. In this lyrical book, Marci Shore evokes the human face of the Ukrainian Revolution. Grounded in the true stories of activists and soldiers, parents and children, Shore's book blends a narrative of suspenseful choices with a historian's reflections on what revolution is and what it means. She gently sets her portraits of individual revolutionaries against the past as they understand it - and the future as they hope to make it. In so doing, she provides a lesson about human solidarity in a world, our world, where the boundary between reality and fiction is ever more effaced. - from bookjacket.